1998
DOI: 10.1159/000027560
|View full text |Cite
|
Sign up to set email alerts
|

<i>Haemophilus influenzae</i> and <i>Streptococcus pyogenes</i> Group A Challenge Induce a Th<sub>1</sub> Type of Cytokine Response in Cells Obtained from Tonsillar Hypertrophy and Recurrent Tonsillitis

Abstract: We have previously shown that tonsil tissue both from children with tonsillar hypertrophy and recurrent tonsillitis is colonized and invaded by Haemophilus influenzae and Streptococcus pyogenes group A. In order to evaluate if these bacteria are involved in the immunopathogenesis of these two conditions, tonsillar cells from both groups were stimulated in vitro with intact, heat-inactivated H. influenzae or S. pyogenes A. The immunoreactivity was evaluated by assessing the induction of cytokine production (IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…A number of studies have shown increased expression of cytokines by T cells from RT compared with HT tonsils, with a predominance of Th1 over Th2 cytokines [43][44][45]. When cells from HT and RT tonsils were stimulated with intact, heat-inactivated Haemophilus influenzae and Group A Streptococcus, H. influenza induced IL-1α, IL-1β, tumour necrosis factor (TNF)-α, IL-6, IL-8, IL-2, interferon (IFN)-γ, TNF-β and IL-10 production in both tonsil groups, but Group A Streptococcus induced significantly higher frequencies of IFN-γ-positive cells in the RT group [46]. Similar findings emerged when T cells from HT and RT tonsils were stimulated with isolated streptococcal M-protein, with S. pyogenes-positive RT tonsil T cells secreting more IFN-γ [45].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown increased expression of cytokines by T cells from RT compared with HT tonsils, with a predominance of Th1 over Th2 cytokines [43][44][45]. When cells from HT and RT tonsils were stimulated with intact, heat-inactivated Haemophilus influenzae and Group A Streptococcus, H. influenza induced IL-1α, IL-1β, tumour necrosis factor (TNF)-α, IL-6, IL-8, IL-2, interferon (IFN)-γ, TNF-β and IL-10 production in both tonsil groups, but Group A Streptococcus induced significantly higher frequencies of IFN-γ-positive cells in the RT group [46]. Similar findings emerged when T cells from HT and RT tonsils were stimulated with isolated streptococcal M-protein, with S. pyogenes-positive RT tonsil T cells secreting more IFN-γ [45].…”
Section: Discussionmentioning
confidence: 99%
“…Different cytokines play key roles in innate immunity to different classes of microbes. Agren et al reported that H. influenzae induced Th1 cytokines in human tonsillar lymphocytes [15]. Harimaya et al demonstrated that Alloiococcus otitidis induced the activation of lymphocytes and the release of Th1 promoting cytokines (IL-12 and IFN-g) during the early phase of the immune response [16].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study indicated the presence of anti-GAS Th1 T cells, but, as whole bacteria were used in their stimulation assays, it cannot be excluded that the observed responses in part derived from innate cells (32). Regarding responses against single proteins, CD4 T cells (directed against GAS M protein) are found in tonsils of patients with recurrent tonsillitis and tonsillar hypertrophy, and these CD4 T cells proliferate and produce cytokines (IFN-g, IL-2, IL-4, IL-5, and IL-6) (33).…”
mentioning
confidence: 99%